Analysis Rasio Likuidity Ratios To Financial Performance Of PT. Medco Energy Internasional Tbk. - Zarman, Nasri; Rusman, Rusman; Al Cassany, Saluddin; Karollah, Banta; Ridha, Ainul; Sijabat, Ferdi Nazirun; Eliana, Eliana (Universitas Muhammadiyah Mataram, 2020)
The purpose of this research is to find out how to analyze the ratio of Liquidity to financial performance in PT. Medco Energi International Tbk. This research uses liquidity ratio parameters. Measurement in terms of liquidity to performance ratio of MedcoEnergi shows that MedcoEnergi Liquidity Ratio capability using carrent ratio, Quick Ratio and Cash Ratio during the two research periods in 2018 and 2019 MedcoEnergi liquidity capability is better than its two competitors Bumi Resources and Elnusa. The advice in this study, should the existing performance be maintained and further improved so that the mission to develop potential energy sources into a profitable investment portfolio continues.Keywords: Financial Performance, Liquidity RatioAbstrak : Tujuan penelitian ini adalah untuk mengetahui bagaimana analisis rasio Likuiditas terhadap kinerja keuangan pada PT.Medco Energi International Tbk. Penelitian ini menggunakan parameter rasio likuiditas. Pengukuran dari segi rasio likuiditas terhadap kinerja MedcoEnergi menunjukkan bahwa kemampuan Rasio Likuiditas MedcoEnergi dengan menggunakan carrent ratio, Quick Ratio dan Cash Ratio selama dua periode penelitian tahun 2018 dan 2019 kemampuan likuiditas MedcoEnergi lebih baik dari dua kompetitornya Bumi Resources dan Elnusa. Saran dalam penelitian ini, sebaiknya kinerja yang telah ada dipertahankan dan lebih ditingkatkan sehingga misi untuk mengembangkan sumber-sumber energi potensial menjadi portofolio investasi yang menguntungkan terus berlanjut. Kata Kunci : Kinerja Keuangan, Rasio Likuiditas